Use of Metaverse for the Development of Digital Entrepreneurship in Nusameta - Susanti, Anissa Lia; Yusuf, Ismail; Rachmani, Nizza Nadya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Entrepreneurs hold an important role in promoting the economic conditions of a state. The government will do anything to improve the business that already exists. In the era of the 4.0 industry business activities have changed into digital activities. The entrepreneurs are expected to maximize the digitalization to improve their business. This digital improvement can be done by using Metaverse. Metaverse could make entrepreneurs able to offer the product to the customer virtually and reach a broader market. Metaverse can also make entrepreneurship activities more flexible. The entrepreneurs can hold virtual exhibitions without seeing consumers directly. By looking at the positive effect of the metaverse, this research will be focused on the use of the metaverse for digital entrepreneurship development in Nusameta, one of the metaverse companies that originate from Jakarta. This research is descriptive qualitative research that collects data by interviewing, observing, and documenting Nusameta’s owner and staff directly. The object of this research is Nusameta a provider that provides a metaverse for digital entrepreneurs. The results of this research showed that Nusameta already provides a metaverse for digital entrepreneurs. The metaverse provided by Metaverse will always be updated according to what is needed by digital entrepreneurs. Nusameta hopes that the update will make entrepreneurs feel comfortable doing business in the metaverse. Nusameta also hopes that the governance can provide new laws that can protect digital entrepreneurs.